2015
DOI: 10.1017/s1754470x15000148
|View full text |Cite
|
Sign up to set email alerts
|

Why has our recovery rate dropped? An audit examining waiting times, starting scores and length of treatment in relation to recovery within an IAPT service

Abstract: Abstract. The Improving Access to Psychological Therapies (IAPT) initiative was created to provide mental health services for those experiencing mild to moderate depression and anxiety. IAPT is commissioned on the basis that it achieves adequate performance on a number of 'key performance indicators', one of which is the proportion of clients who 'move towards recovery' following treatment. The impetus for the current evaluation was a significant reduction in the proportion of clients recovering within an IAPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
(12 reference statements)
1
7
0
Order By: Relevance
“…Accepting the confounding factors potential impact on the results, this study does raise the possibility that a progression model, with cases being treated at step 2 in the first instance, may achieve better recovery rates for those scoring more severely initially than those within a stratified model. This supports other studies that found no difference in the initial score severity between those treated at low or high intensity [11], or scores not to be an influencing factor on a service achieving low or high recovery rate [12]. One systematic review [10] found considerable variation of patient severity and symptom chronicity and no clear trends that related chronicity/severity to clinical outcome.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Accepting the confounding factors potential impact on the results, this study does raise the possibility that a progression model, with cases being treated at step 2 in the first instance, may achieve better recovery rates for those scoring more severely initially than those within a stratified model. This supports other studies that found no difference in the initial score severity between those treated at low or high intensity [11], or scores not to be an influencing factor on a service achieving low or high recovery rate [12]. One systematic review [10] found considerable variation of patient severity and symptom chronicity and no clear trends that related chronicity/severity to clinical outcome.…”
Section: Discussionsupporting
confidence: 77%
“…Another study compared outcomes of low and high intensity treatment and found no difference in baseline scores between low or high intensity treatments [11]. Similarly, a different study [12] found initial scores were not an influencing factor on a service achieving low or high recovery rates. A systematic review [10] found considerable variation of patient severity and symptom chronicity and no clear trends that related chronicity/severity to clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study by Marshall et al (2016) found that the rigidity of the service and the waiting process were also the main contributing factors for discontinuation of therapy. Although there were no differences found between factors contributing to drop-out rates amongst psychological treatment approaches (Grant et al, 2012;Hembree et al, 2003;Vaillancourt et al, 2015), the nature of the therapeutic alliance seems to correlate with therapy drop-out (Sharf et al, 2010). The crucial role that the therapeutic relationship plays on positive progress in CBT treatments has been highlighted elsewhere (Cooper et al, 2016;Easterbrook and Meehan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Few survey participants indicated that their clients routinely received a grossly inadequate number of sessions, with almost all participants indicating that they routinely provided either 7–12 sessions or 13–20 sessions, with the latter category being more common for complex cases. This is an important finding as recent studies have indicated that higher numbers of treatment sessions are associated with better clinical recovery (Gyani, Shafran, Layard and Clark, 2011; Vaillancourt, Manley and McNulty, 2015). The 3 rd Annual IAPT Report (HSCIC, 2015) paints a less rosy picture, with the national average for CBT sessions being 5.8.…”
Section: Discussionmentioning
confidence: 67%